Management of bare root complete overdenture in patients with a history of methamphetamine abuse: A case report - Livia IF. Enggarsetia; Muslita Indrasari (Indonesian Journal of Prosthodontic, 2025)
Methamphetamine abuse has severe consequences on oral health, commonly leading to rampant caries, advanced periodontal disease, and early tooth loss. These patients frequently become edentulous at a relatively young age. In such cases, a bare root overdenture can be an effective treatment option. This report aims to present the advantages of a bare root complete overdenture for a patient with a history of methamphetamine abuse. A 44-year-old male presented with multiple missing teeth in both arches and a history of non-prescription methamphetamine use for approximately 17 years, with abstinence over the past 7 years. This resulted in dry mouth and extensive tooth decay. Additionally, he had been a heavy smoker for the past 28 years. Clinical examination revealed the absence of teeth 18–16, 14–22, 26–28, 31–38, and 45–48. Radiographic analysis showed that the retained roots of teeth 23–25 and 42-44 were relatively long (9–12 mm) with no mobility. After recording tentative vertical dimension and evaluating the occlusal plane, teeth 15, 23–25, and 41–44 were found to be extruded by 4–6 mm. Tooth 15 and 41 were extracted due to poor prognosis. A bare root complete overdenture supported by abutment teeth 23–25 and 42–44 was selected due to severe tooth extrusion and limited interocclusal space. In this case, the bare root complete overdenture improved the retention, support, and stability of the prosthesis, enhancing the patient's quality of life. Oral hygiene improved after drug cessation, enhancing long-term prosthesis outcome.